Cardiac metabolic stress during ischemia and reperfusion in patients undergoing coronary artery bypass surgery using either calafiore or modified Del Nido cardioplegic solutions - Massa, Abd Alhade; Izzat, Ahmad Walid; Saadoun, Rakan; Izzat, Mohammad Bashar (Journal of cardiac surgery, 2024)
Objective: Calafiore and modified del Nido cardioplegic solutions are currently being used during coronary artery bypass surgery. This study aims to compare myocardial ischemic stress associated with both solutions by studying the changes in cardiac metabolites during cardioplegic ischemic arrest and early reperfusion. Methods: Biopsy specimens were taken from the left ventricles of 20 patients undergoing routine coronary artery bypass grafting using Calafiore or modified del Nido cardioplegic solutions. Biopsies were taken immediately after the beginning of extracorporeal circulation (basal biopsy), 30 min after application of the aortic cross-clamp (ischemic biopsy), and 20 min following the removal of aortic cross-clamp (reperfusion biopsy) and were analyzed for their amino acid and lactic acid contents using amino acid analyzer and appropriate kits. Peripheral blood samples were also collected for the determination of blood concentrations of cardiac proteins (CK-MB and troponin I) using an immunofluorescence scanner. Results: Both CK-MB and troponin I increased significantly 12 h postoperatively and were associated with an increase in myocardial lactic acid, but there were no significant differences in markers of myocardial injury between the two groups. Comparison of amino acid concentrations between the two groups according to sampling time showed that glutamic acid concentrations were significantly lower in the Calafiore cardioplegia group compared to the del Nido cardioplegia group, but there were no other significant differences in markers of metabolic stress (taurine and alanine/glutamate ratio) between the two groups. Moreover, there were no significant differences in changes in amino acid concentrations regardless of the type of cardioplegic solution used. Conclusions: Cardioplegic ischemic arrest and early reperfusion are associated with a rise in myocardial metabolic stress. Both Calafiore and modified del Nido cardioplegic solutions are effective in attenuating myocardial substrate derangements and confer equal myocardial protection during routine coronary artery bypass surgery. Trial Registration: ClinicalTrials.gov identifier: NCT06287372
Gesehen am 08.04.2025